Integração entre sistema embarcado e banco de dados no Excel aplicados ao controle automático - Kisine, Blenda Akemi [UNESP] (2024)
This work presents the development of an automation system that integrates Microsoft Excel, through VBA (Visual Basic for Applications) programming, with the Arduino microcontroller for LED control. The objective is to explore the capabilities of Excel as a tool for data storage and manipulation in low-cost projects, as well as to evaluate its feasibility as a complementary solution for databases in automation applications. Through an interactive form in Excel, the data is entered, updated, and sent to the Arduino, which activates different LEDs according to the specifications of the received values. The communication between Excel and Arduino is mediated by a Python script, which allows data exchange via the serial port, providing an immediate visual response. Several tests were conducted to ensure the stability and accuracy of the system. The results demonstrate that the combination of Excel, VBA, and Arduino offers a practical solution for simple automation and hardware control projects, contributing to the understanding of the limitations and potential of these tools in a context of automation and data manipulation.